Narrativas de si e do outro: um projeto de letramento a partir da leitura e da produção de memórias em sala de aula de Língua Portuguesa - Heliabe Xavier Nogueira (2023)
The present work is based on the conception of literature that enables the development of sensitivity, expands the world view, awakens emotions and has the power to exercise fantasy and imagination, in addition to making us reflect on our own existence. This concept is the basis of the literacy project presented here, which aims to train literary readers based on reading and the multimodal production of memories. In this sense, the objective of this investigation is to propose the reading and writing of literary memories to students in the final years of elementary school through didactic sequences, motivating them to revisit their most remote reading memories, re-signify them and share them. With this experience, we seek to enable new practices for teaching literary reading in the classroom, through activities that are organized around a temporal and historical perspective: the memory of the other (writers), the memory of the self in the present and the memory of the self in prospect of a near future. This is a research with a qualitative approach, with a propositional character, in line with the paradigms of intervention research, according to Damiani (2012) and Bortoni-Ricardo (2008). The methodological theoretical framework is based on Candido (1995), Todorov (2009), Compangnon (2012), Cosson 2009), Bakhtin (1992, 2016), Benjamin (1987), Leal (2006, 2007), Aragão (1992), Chiaretto (2013), Machado (2016), Lessa (2013) and in the guidelines on language practices present in the Base Nacional Comum Curricular (BNCC): Educação Infantil e Ensino Fundamental document (BRASIL, 2018). The results of the study and the elaboration of didactic sequences through memory lead us to deduce that it is possible to provide students with literary literacy based on their literary reading experiences, their subjectivities, their memories, their feelings and attributed values to literary reading at different moments of life, as a representation of oneself and one's history as a subject reader.